Review of guideline for the management of ANCA-associated vasculitis, presented in 2021 by the American College of Rheumatology/Vasculitis Foundation - T. V. Beketova; I. Yu. Popov; V. V. Babak (Научно-практическая ревматология)
The anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAVs) are a group of severe life-threatening autoimmune diseases, and one of the most important problems in practical rheumatology. This article discusses 2021 American College of Rheumatology/Vasculitis Foundation guideline for the management of AAVs, including granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic granulomatosis with polyangiitis (EGPA). The guideline features 26 recommendations and 5 upgraded position statements for GPA/ MPA, as well as 15 recommendations and 5 upgraded position statements for EGPA, which became the basis for the proposed algorithms for the treatment of patients with GPA/MPA and EGPA. Particular attention has been paid to the use of biologics.